2021
DOI: 10.33365/joupe.v2i1.950
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Siswa Terhadap Proses Penerapan Pembelajaran Pendidikan Jasmani Olahraga Dan Kesehatan Pada Pandemi Covid-19

Abstract: This study aims to find out about students' perceptions of the process of implementing sports and health physical education learning in the covid-19 pandemic at SMA Negeri 1 Padang Cermin.   This research is a quantitative descriptive.  The method used is a survey with data collection techniques using a questionnaire.  The population in this study was 588 students consisting of class X and XI at SMA Negeri 1 Padang Cermin and the sample of this study was 88 students in class X and XI. The data analysis techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
0
5
0
12
Order By: Relevance
“…Various studies have shown that the perceptions obtained by students have a major influence on the understanding of the PJOK concept and the motivation of students to participate in the learning process (Hariadi, 2021;Melyza & Aguss, 2021;Rustiana, 2011;Sobarna dkk., 2020;Yulianingsih & Parlindungan, 2020). The existence of this positive relationship will help lecturers or teachers in achieving learning objectives, considering that knowledge received positively by students will also provide a positive perception of PJOK learning which in turn will have a positive impact on students who have negative assumptions about this course (Hariadi, 2021;Mulya & Agustryani, 2020;Setiawan, 2017;Sulistyono, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown that the perceptions obtained by students have a major influence on the understanding of the PJOK concept and the motivation of students to participate in the learning process (Hariadi, 2021;Melyza & Aguss, 2021;Rustiana, 2011;Sobarna dkk., 2020;Yulianingsih & Parlindungan, 2020). The existence of this positive relationship will help lecturers or teachers in achieving learning objectives, considering that knowledge received positively by students will also provide a positive perception of PJOK learning which in turn will have a positive impact on students who have negative assumptions about this course (Hariadi, 2021;Mulya & Agustryani, 2020;Setiawan, 2017;Sulistyono, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Description: P = The percentage calculated from the number of respondents' answers F = Frequency (number of scores obtained) N = Number of respondents Categorization uses the mean and standard deviation. Azwar in [15] states to determine the score criteria using Norm Reference Assessment (PAN) as in Table 1.…”
Section: Data Analysis Techniquesmentioning
confidence: 99%
“…Populasi merupakan keseluruhan subjek baik orang atau benda yang memenuhi kriteria yang dibutuhkan oleh peneliti sehingga dapat dijadikan objek penelitian yang membuahkan hasil (Melyza & Agus, 2021). Populasi penelitian ini mencakup siswa kelas IV SDN Kalisari 02 Pagi dengan total keseluruhan sebanyak 60 siswa.…”
Section: Metodeunclassified